THE COMMON CHARACTERISTICS OF COTTON FISHING NET TWINES-EXPERIMENT SERIES II* - Kuriyan, G K; Cecily, P J (Indian Journal of Fisheries, 2016)
The essentials to the economic well being of a developing national industry are the availability and the production of the basic raw materials within the concerned country. The Indian fishing industry, as the mainstay to ensure progress in exploitation, depends on fibres of vegetable origin. The majority of these fibres, cotton (Gossipium spp.) being the most important among them, arc pro.ured from indigenous sources. Notwithstanding the increasing demand from the Textile and other alUed industries, a fair percentage of the country's annual production of cotton fibres, twisted in the form of threads, twines and ropes, is consumed by the fishing industry for fabrication of nets and other gear. Regardless of the importance as a net material, it must be admitted that very little information is available on record evaluating the dynamic characteristics of cotton twines. In an earlier communication (Kuriyan and Cecily, 1959) the authors presented an account of the preliminary studies conducted by them for the evaluation of the common characteristics of cotton fishing net twines. The present paper describes the Second Experiment Series in these investigations and embodies the results of analysis of a separate set of Indian machine twisted twines. While the first set were 'Soft' twisted,.the present series comprise of samples with 'Hard' twist.